Common variants in the regulative regions of GRIA1 and GRIA3 receptor genes are associated with migraine susceptibility - Gianfrancesco Fernando; Griffiths Lyn R; Diodato Daria; Farina Olimpia; Sampaolo Simone; Aloia Andrea; Formicola Daniela; Di Iorio Giuseppe; Esposito Teresa (BMC Medical Genetics, 2010)
Abstract Background Glutamate is the principal excitatory neurotransmitter in the central nervous system which acts by the activation of either ionotropic (AMPA, NMDA and kainate receptors) or G-protein coupled metabotropic receptors. Glutamate is widely accepted to play a major role in the path physiology of migraine as implicated by data from animal and human studies. Genes involved in synthesis, metabolism and regulation of both glutamate and its receptors could be, therefore, considered as potential candidates for causing/predisposing to migraine when mutated. Methods The association of polymorphic variants of GRIA1-GRIA4 genes which encode for the four subunits (GluR1-GluR4) of the alpha-amino-3- hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptor for glutamate was tested in migraineurs with and without aura (MA and MO) and healthy controls. Results Two variants in the regulative regions of GRIA1 (rs2195450) and GRIA3 (rs3761555) genes resulted strongly associated with MA (P = 0.00002 and P = 0.0001, respectively), but not associated with MO, suggesting their role in cortical spreading depression. Whereas the rs548294 variant in GRIA1 gene showed association primarily with MO phenotype, supporting the hypothesis that MA and MO phenotypes could be genetically related. These variants modify binding sites for transcription factors altering the expression of GRIA1 and GRIA3 genes in different conditions. Conclusions This study represents the first genetic evidence of a link between glutamate receptors and migraine.